Cultural Backlash? How (Not) to Explain the Rise of Authoritarian Populism. Issue 4 (24th October 2022) - Schäfer, Armin
Abstract: This book review examines the theory of populism advanced by Pippa Norris and Ronald Inglehart in Cultural Backlash . The authors offer a distinct explanation of the rise of authoritarian populism in advanced democracies. As societies become more liberal over time, older, more conservative cohorts feel under threat of losing majority status and allegedly turn towards authoritarian-populist parties that promise to stop the tide of liberalism. However, this theory of populism finds little empirical support. In contrast to what the authors argue, there is no polarization of attitudes between younger and older cohorts, and younger cohorts are more likely to vote for authoritarian-populist parties. To substantiate this claim, I replicate many of the analyses in Cultural Backlash and add additional ones with the newest wave of the European Social Survey and the Chapel Hill Expert Survey. I conclude by observing that while the cultural backlash theory of populism does not hold, this does not invalidate cultural approaches more generally.